ANALISIS FAKTOR FAKTOR DALAM PARTISIPASI MASYARAKAT PADA PEMBANGUNAN DESA WISATA GENTING KABUPATEN SEMARANG - Yusuf Manggala; Moch. Mustam (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
The problem in this research is the less optimal of society’s participation in Genting village Semarang regency. This research aims to know the level of society’s participation and the factors which are related to society’s participation in Genting. This research applied explanatory research by using quantitative approach. The result of this research indicated that there is a positive relationship of internal factor of age (r=0,202), education (r=0,203;), occupation (r=0,222), and distance (r=0,204). The external factor of leadership showed the relation with a negative correlation coefficient (r=-0,250) and positive relation of communication (r=0,106). It means that, the more young citizen who participate. Then, the more of high education citizen participate in, the more working citizen who participate. In addition, the distance from citizen’s house to village administration which is more closer, the good leadership in the village, and the use of communication will increase the level of citizen participation. The internal factors of participation are, age, education, occupation, and distance. Therefore to increase the citizen’s participation, it can be done by increasing female participation through Female Welfare Program (PKK), increasing the role of youth through KARANG TARUNA or POKDARWIS, giving training to high school graduation citizen. Besides, increasing the role of working citizen and citizen whose home is near from village administration in tourism village activity is also can be done. On external factors, improving the leadership attitude which can adjust citizens’ need can be done to improve the participation. The improvement of participation also can be done through technology literate and the use of communication media such as social media.